Anodal Transcranial Direct Current Stimulation Reduces Secondary Hyperalgesia Induced by low Frequency Electrical Stimulation in Healthy Volunteers - Vo, Lechi; Ilich, Nicole; Fujiyama, Hakuei; Drummond, Peter D. (The journal of pain, 2022)
•Transcranial direct current stimulation (tDCS) at the motor cortex (M1) increased pain threshold.•tDCS over the dorsolateral prefrontal cortex (DLPFC) reduced secondary hyperalgesia.•Concurrent tDCS over M1 and DLPFC did not evoke greater analgesia than tDCS at M1, DLPFC, or sham. The aim of the study was to determine whether transcranial direct current stimulation (tDCS) reduced pain and signs of central sensitization induced by low frequency electrical stimulation in healthy volunteers. Thirty-nine participants received tDCS stimulation under 4 different conditions: anodal tDCS of the primary motor cortex (M1), anodal tDCS of the dorsolateral prefrontal cortex (DLPFC), anodal tDCS over M1 and DLPFC concurrently, and sham tDCS. Participants were blind to the tDCS condition. The order of the conditions was randomized among participants. Pain ratings to pinpricks, the current level that evoked moderate pain, and pain induced by low frequency electrical stimulation were assessed in the forearm by an experimenter who was blind to the tDCS conditions. Anodal tDCS at M1 increased the current level that evoked moderate pain compared to sham and other conditions. Anodal tDCS of DLPFC completely abolished secondary hyperalgesia. Unexpectedly, however, concurrent anodal tDCS over M1 and DLPFC did not reduce pain or hyperalgesia more than M1 alone or DLPFC alone. Overall, these findings suggest that anodal tDCS over M1 suppresses pain, and that anodal tDCS over DLPFC modulates secondary hyperalgesia (a sign of central sensitization) in healthy participants. Anodal transcranial current stimulation (atDCS) at the left motor cortex and the dorsolateral prefrontal cortex increased the electrically-evoked pain threshold and reduced secondary hyperalgesia in healthy participants. Replication of this study in chronic pain populations may open more avenues for chronic pain treatment.